Study of Forms and Meanings Simalungun Folk Song Urdo-Urdo in Bahapal Raya Village - Sara Dewanti Purba (Gondang: Jurnal Seni dan Budaya, 2023)
This study aims to determine the origins of Urdo-urdo chants, to know the study of Urdo-urdo chants, to find out the forms of Urdo-urdo chants, to find out the meaning contained in Urdo-urdo chants, and to find out the characteristics of Urdo-urdo chants in Bahapal Raya Village, Pematang Raya District, Simalungun Regency. The theoretical basis used in this study is the theory of study which explains the meaning of study, namely or describes a detailed matter so that it conducts a study; music theory, namely music is a cultural activity that is very familiar with human life, form theory, namely form is a scheme or arrangement that intact from several phrases, the theory of meaning that uses semiotic theory and semantic theory, the theory of Urdo-urdo songs, namely those that function as lullabies and songs to calm crying children. The research method used in this study is a qualitative descriptive method. Based on the results of the research conducted, it can be seen that the origin of Urdo-urdo singing is an ethnic song passed down from the ancestors of the Simalungun people to their generation orally. The hallmark of Urdo-urdo singing is using Iggou Simalungun. The Urdo-urdo singing form consists of four forms: A, B, C, and D. The meaning contained in the Urdo-urdo singing presented by the resource person is a lullaby for children, which contains advice..